Koblinger mellem økonomi og uddannelse - Christian Ydesen; Karen E. Andreasen (Educare)
Public administration of education systems after World War Two has been characterized by the increasing involvement of various forms of evaluation and performance measurement. By taking up such a central role, the various forms have had considerable impact on school pedagogy. At the same time, education systems have more and more come to be seen as levers for economic growth and prosperity, which in turn has strengthened and expanded these practices of evaluation and performance measurement. We argue that post-war educational accountability practices have taken on a new character where quantification, in light of economic concerns, gradually have taken pride of place. Paradoxically, the emerging welfare states have been committed to democratic ideals about inclusion and equal access to education. Such ideals are naturally followed by questions about social differentiation; and in that sense, they question whether an economistic approach to education in fact challenges the democratic values and processes expressed in the very purpose of education. Using Denmark as an example, the article explores these processes and questions by looking at the development and historical roots of the Danish public-school system.